2007
DOI: 10.1590/s0102-311x2007001100022
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate and energy expenditure during garbage collection in Rio de Janeiro, Brazil

Abstract: Physiological workload is used to estimate the physical demand of tasks in the workforce

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
3
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 13 publications
4
10
3
8
Order By: Relevance
“…As for many developing countries, there are very few data on BMR in Brazilian samples. Absolute BMR values for men and women of Niterói were similar to the values of seventy male garbage collectors of mean age ,37 years (5888?2 (SE 106?2) kJ/d) (30) and eighty-one collegeaged women (4819?1 (SE 74?3) kJ/d) living in Rio de Janeiro, but lower than the values of forty-eight students of college age (twenty-three women) from southern Brazil (31) . Rodrigues et al (32) retrospectively analysed resting energy expenditure data of 760 Brazilian female participants in a hospital setting and the results were higher than the values found for women from Niterói.…”
Section: Discussionsupporting
confidence: 64%
“…As for many developing countries, there are very few data on BMR in Brazilian samples. Absolute BMR values for men and women of Niterói were similar to the values of seventy male garbage collectors of mean age ,37 years (5888?2 (SE 106?2) kJ/d) (30) and eighty-one collegeaged women (4819?1 (SE 74?3) kJ/d) living in Rio de Janeiro, but lower than the values of forty-eight students of college age (twenty-three women) from southern Brazil (31) . Rodrigues et al (32) retrospectively analysed resting energy expenditure data of 760 Brazilian female participants in a hospital setting and the results were higher than the values found for women from Niterói.…”
Section: Discussionsupporting
confidence: 64%
“…The value from the mean heart rate per day for 314 GC worker-days measured in the winter of 1996 in Brazil (from June to November) was 97.6 ± 10.6, and the value from an mean heart rate for 308 GC worker-days at P act (mean time: 293 min) was 104.0 ± 11.7 10) . The value computed from the mean heart rate per day of 3 LOADER and 3 SOLO workers over 3 days in this study was 97.5 ± 11.8, approximately the same value as the results in the above 2 studies.…”
Section: Activity Intensitymentioning
confidence: 88%
“…From heart rate measurement results of the GC, Kemper et al 7) and Luttmann et al 8) clarified that breaks of sufficient time and frequency are necessary, allowing GC to recover until their heart rate is not considered problematic. Anjos et al 9,10) also revealed the actual conditions of the workload by measuring the heart rate of GC, and appealed to set a limit on working hours in order to protect the health of workers in developing countries. In Japan, the Ministry of Labour issued a notice for disaster prevention to cleaning businesses in 1993 11) .…”
Section: Introductionmentioning
confidence: 99%
“…A execução da tarefa de coleta de lixo pode ser feita de forma manual, semiautomatizada ou automatizada, variando de acordo com o desenvolvimento tecnoló-gico do local, características demográficas da região e nível educacional e cultural da população 2 . Contudo, esta atividade está entre as ocupações de maior risco para a saúde dos trabalhadores 3. Os coletores de lixo estão constantemente expostos a esforços físicos durante a realização de suas atividades laborais, os quais envolvem caminhadas, corridas, subidas e descidas de ladeiras e levantamento e transporte de pesos variados ao longo do dia 4,5 . Um estudo realizado por Anjos e colaboradores 6 , concluiu que o gasto energético de um coletor de lixo durante o trabalho variou entre 288,4 e 319,1 kcal por hora, podendo alcançar um gasto de até 2000 kcal por período de trabalho, caracterizando o trabalho como pesado, de acordo com a Organização Mundial de Saúde.…”
Section: Introductionunclassified
“…Apesar de alguns estudos determinarem a exigência física e ergonômica desses trabalhadores 5,6 , ainda são escassas as pesquisas que avaliam esse tema específico. Portanto, o objetivo do presente estudo foi determinar o nível de atividade física (AF) total e nos diferentes domínios (lazer, deslocamento, ocupacional e doméstico) dos coletores de lixo de duas cidades de porte médio do Rio Grande do Sul/Brasil.…”
Section: Introductionunclassified